Laboratory development of a vertically oriented penetrometer for shallow seabed characterization - Fauzan, Sahdi; White, David J.; Gaudin, Christophe; Randolph, Mark F.; Boylan, Noel (National Research Council of Canada, 2015)
Current site investigation practice for offshore pipeline design relies on soil parameters gathered from boreholes or in-situ test soundings to depths of 1-2 m below the mudline. At these depths, the fine-grained seabed is very soft and possesses low undrained strength, which can be difficult to measure. This paper describes a centrifuge test programme undertaken to evaluate the feasibility and performance of a novel penetrometer designed to assess the shallow strength of soft seabed over continuous horizontal profiles. This device is termed the vertically oriented penetrometer (VOP). Tests were performed on a normally consolidated kaolin sample, with the VOP translated horizontally at velocities ranging from 1 – 30 mm/s, after embedding the VOP at 30 mm and 45 mm depths. All tests involved many cycles of VOP forward and backward movement to assess its potential to derive the ratio of intact to fully remoulded strength. Strength determination is achieved by dragging the VOP at a specified embedment depth along the soil surface, and deriving the soil strength from the measured resistance as if the VOP were a laterally loaded pile. The VOP is shown to yield comparable strength measurements to that of a T-bar penetrometer. The VOP is a potentially valuable addition to the range of tools used to characterize soil strength, both in small scale centrifuge models and, following practical development, potentially also in the field.